2020
DOI: 10.1108/ijcthr-11-2019-0194
|View full text |Cite
|
Sign up to set email alerts
|

The role of servicescape and social interaction toward customer service experience in coffee stores. The case of Vietnam

Abstract: Purpose This study aims to investigate the effects of servicescape on customer satisfaction and loyalty – centered on social interaction and service experience in the café setting. Design/methodology/approach Data for this study were collected from approximately 1,800 customers at 185 coffee stores located in the three largest cities in Vietnam through the self-administered questionnaires. Findings The research findings pointed out the significant impacts of café servicescape on social interaction quality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 81 publications
3
45
0
4
Order By: Relevance
“…These results will add value to those responsible for fitness centers in making decisions to improve customer loyalty [ 13 ]. Therefore, our findings confirm previous studies from different sectors that showed that servicescape has a positive relationship with consumer loyalty [ 29 , 30 , 32 ]. In fact, this research aligns Ong and Yap´s (2017) study in which it was indicated that servicescape had a positive influence on consumers behavioral intentions in fitness centers [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results will add value to those responsible for fitness centers in making decisions to improve customer loyalty [ 13 ]. Therefore, our findings confirm previous studies from different sectors that showed that servicescape has a positive relationship with consumer loyalty [ 29 , 30 , 32 ]. In fact, this research aligns Ong and Yap´s (2017) study in which it was indicated that servicescape had a positive influence on consumers behavioral intentions in fitness centers [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…Others, such as Madzharov, Block and Morrin (2015), also examined how ambient scents affect consumers’ perceptions and feelings and, subsequently, their purchase intention [ 28 ]. Recently, the study of Tran, Dang and Tournois (2020) has revealed the positive relationship between servicescape and consumer loyalty in coffee stores [ 29 ], as also indicated by the studies of Lee, Fu and Tsai (2019) and, Rai and Anirvinna (2019) [ 30 , 31 ]. Regarding studies that have analyzed both variables in the sports sector, Hightower, Brady, and Baker (2002) showed that there was a positive relationship in sporting event customers [ 32 ].…”
Section: Theoretical Foundationmentioning
confidence: 93%
“…Consequently, the perception of innovativeness in terms of touchless technologies in tourism positively influences the visitors' behavioral intention (i.e. revisit intention) (Tran et al, 2020). This study focused on consumers' viewpoints of the future of contactless services and considered their readiness to receive the service by employing the consumer innovativeness theory.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…On the other hand, a few research works have inquired about the impacts of the communicative staging of the sustainable servicescape in a hospitality context [9,29]. This study also encompasses the industry gap as earlier research was conducted in various categories of the hospitality field such as casual dining [30], coffee stores [31], opera events [32], airports [33], and health care settings [34], while the present research is executed in boutique hotels in Pakistan.…”
Section: Introductionmentioning
confidence: 99%